MODEL FRAMEWORK OF PROFITABILITY OF INDONESIAN TELECOMMUNICATION COMPANY - Mu’tamaria Mu’tamaria; Ahmad Ariq Rabbani; Agus Sukoco; Gede Arimbawa; Liem Gai Sin (Journal of International Conference Proceedings (JICP), 2018)
The purpose, The purpose of this research is to know the profitability ratios of telecommunication companies listed in Indonesia Stock Exchange period 2013-2015, particularly the influence of profitability ratio to stock price of telecommunication company Method, This research is conducted on seven telecommunication companies listed in Indonesia Stock Exchange period 2013-2015 The data used are secondary data of financial statements. The analytical technique mobilize multiple linear regression with two dependent variables of ROA and ROE and one free variable of stock price, to test the contribution of variable in influencing the stock price of companies. The test is done with SPSS version 20 software. Result, The results of research on Indonesian telecommunications companies show that the movement of stock prices are not significantly influenced by the value of ROA and ROE on Indonesian telecommunications companies. The findings This study found that in the telecommunications company in Indonesia the increased or decreased value of ROA and ROE did not give effect on the movement of stock prices of companies. This is different from other corporate lines in which stock prices are vulnerable to changes of ROA and ROE values. Keywords: ROA, ROE, corporate, telecommunications